The microbiological quality of bottled and tap water: Risks and regulations - J. L. Maselela; M.M Mokoena; M. I. Mokgobu; L. S. Mudau (Sustainable Environment)
Bottled water (BW) is widely used and distributed in South Africa (SA), with limited assessment of its quality. Different brands are distributed and sold in formal (licensed i.e. supermarkets, restaurants, convenient shops) and informal (unlicensed i.e. street and food vendors, Spaza) shops with less accountability for their safety. Counterfeit BW of well-known brands was purported to be distributed in the Emfuleni Local Municipality (ELM) which could have been exacerbated by drinking water contamination reported in the area. A total of 15% diarrhoea cases for children under the age of 5 was recorded. Although there were concerns of poor quality of BW in the community, no comprehensive study has assessed the microbiological quality of both bottled water and tap water (TW). The aim of the study is to determine the compliance of TW and BW to SANS 241 & 1657 standards for total coliform (TC) and E.coli. The Colilert method was used to assess TC, E.coli, and HPC. Observations were carried out using a checklist to observe how BW for sale was handled and stored. Data was analysed using the Statistical Package for Social Sciences (SPSS) version 27. TW was free of TC and E. coli. In contrast, TC and E. coli were detected in BW. The HPC was found in 47 out of 84 samples (56%) of tap and 95 out of 117 samples (81%) of BW, respectively. TW was of a better quality to BW. Stringent measures on BW should be intensified to protect public health.